Multiple rare abdominal aortic branch variations in the case of a centenarian woman. Case report and review of the literature - Michela Vincis; Claire Lewis; Denis Barry; Marcello Trucas (Translational Research in Anatomy)
Background: Anatomical variations of the abdominal aorta are crucial when considering the success of clinical procedures including diagnostic imaging, oncologic resections, organ transplantations, laparoscopic surgeries, management of penetrating abdominal injuries, and interventional radiological procedures. Accurate knowledge of these vessels is essential for these procedures to be effective. The literature underlying the relationships of the anterior visceral branches of the aorta, especially regarding their origins and distances from the aortic bifurcation, is limited. As part of routine anatomical dissection, we identified multiple rare aortic vessel variants in a cadaveric female with associated visceral adaptations. Methods: A 99-year-old formalin embalmed female donor was dissected at the Discipline of Anatomy, School of Medicine, Trinity College Dublin. The branches of the abdominal aorta were isolated, and their course and relationships with related abdominal organs were visualised. Results: A ptotic arrangement of the liver, pancreas, stomach and gall bladder displacement, and multiple rare aortic branch variants were identified, including variations in the inferior phrenic arteries, a long hepatosplenic trunk, a long cystic artery originating from the gastroduodenal artery, the anterior origin of the right renal artery adjacent to the superior mesenteric artery, and the bilateral absence of the ovarian arteries. Conclusions: These variations, combined with the inferior displacement of several abdominal viscera make this case exceptionally rare and significant for its potential clinical and surgical implications. This work demonstrates how the simultaneous presence of multiple rare abdominal vascular variations, and the concomitant displacement of abdominal organs has led to a complete adaptation of the vascular system and organ function. The donor had reached almost one hundred years of age without any significant symptoms, demonstrating how a systemic study of the patient is important prior to surgical intervention, where the presence of vascular variants is suspected.